Pengaruh Motivasi Belajar Terhadap Hasil Belajar Matematika Siswa SMP - Maria Lina Keban; Selestina Nahak; Yoseph Pius Kurniawan Kelen (Saintek Lahan Kering, 2018)
This study entitled The effect of learning motivation towards Junior high school students' result of learning math. This study aims at finding out the effect of learning motivation towards students' result of learning Math and how significant/big the learning motivation affects the result of learning Math. The population in this study are the entire students of Junior High School 1 North Insana which consists of 219 students. The sample of this study are all students of grade IX of Junior High School 1 North Insana which consists of 58 students. The variables in this study are students' motivation as the unbound/free variable (X) and the result of learning as the bound variable. The technique of data collection used is test of result of learning and learning motivation questionnaire as the primary data. Simple regression analysis is used to test the hypothesis with the equation of regression as Y=39.11 + 0.51x. After testing with simple regression analysis, it is concluded that there is a strong effect between learning motivation towards the result of learning Math which is shown by the result of the counting of coeficient correlation as 0.715 seen from the interpretation table of correlation coeficient of r score/value and the result of the counting of determination coeficient as 71.5% which means the more the learning motivation the better the learning result